Calcium cross-linked zwitterionic hydrogels as antifouling materials. (June 2020) - Chan, Hsi-Min; Erathodiyil, Nandanan; Wu, Hong; Lu, Hongfang; Zheng, Yiran; Ying, Jackie.Y.
Abstract: Current biomedical devices often suffer in lifetime due to proteins, cells and bacteria adherence to the implants, forming dense collagenous capsule around these implants. Bio-fouling and foreign body reactions would induce inflammatory responses, and may give rise to infection and/or implant rejection. Antifouling materials are widely used to combat this costly and complicated problem. However, existing materials do not completely prevent foreign body reactions, and hence, may not be suitable for long-term in vivo applications. Herein we show that cross-linking polymers with calcium and a zwitterionic amino acid monomer, methacryloyl-l -lysine (MLL), produces a novel antifouling, biocompatible hydrogel. We used 6 common acrylate monomers and different concentrations of MLL to create this material. Hydrogel with 30 mol% MLL was best at preventing the attachment of cells, proteins and bacteria. The ultralow-fouling hydrogel resisted the formation of capsule for at least 2 months when subcutaneously implanted in mice. The zwitterionic hydrogels are chemically defined, inexpensive to make, highly porous, and moldable. They are promising as antifouling biomaterials that may improve the performance of medical devices such as biosensors, drug-releasing devices, tissue scaffolds and artificial organs.